Pluralism of Religion Based on Sharia as An Anticipation of Intolerance in Muslims Majority Countries of The Southeast Asian - Syariful Alam; Happy David Pradhan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Religious pluralism is a constructive attitude encompassing not only theological and normative awareness but also social awareness, acknowledging the reality of living in a pluralistic society with diverse religions, cultures, ethnicities, and social structures. Religious pluralism must also be understood as an authentic appreciation for diversity. It involves the acceptance of various religions and is employed in multiple contexts. Pluralism seeks to deconstruct absolutism, promote relativism, and establish a foundation of tolerance for differences and heterogeneity. It views pluralism not merely as a fact to be recognized but also as a positive force to be celebrated and utilized constructively. This study employs a qualitative methodology, utilizing textual analysis of religious and philosophical literature to explore the theoretical and practical dimensions of religious pluralism. The findings reveal that religious pluralism functions as a unifying force across societal strata, fostering cohesion and integration. A pluralist must not only acknowledge but also actively defend diversity and heterogeneity as valuable assets. However, the research highlights ongoing challenges in societal perceptions, where misunderstandings and differing interpretations of pluralism and multiculturalism—often influenced by personal perceptions rather than sharia-based principles—persist. This study contributes to the discourse on religious pluralism by providing a nuanced analysis of its potential to bridge differences and foster coexistence in diverse societies. It also offers a framework for addressing misconceptions, emphasizing the importance of aligning pluralistic values with broader socio-religious principles.